Penelitian Pengaruh Penggunaan Beberapa Jenis Adjuvant Pada Formulasi Pestisida Bentuk Water Dispersible Granule (Wdg) - Emmy Ratnawati; Hendartini Hendartini; Sumingkrat Sumingkrat (Jurnal Kimia dan Kemasan, 2001)
The adjuvant usage gives an effect in the Water Dispersible Granule of pesticide formulation, both for types of adjuvant or its concentration. Binding agents as a part of adjuvant use in this research are Poly Vinyl Pirolidone, Poly Vinyl Alcohol, CMC and Gum Arabic. The best sequence formulation for water dispersible granule on active ingredient, speed of desintegration and pH (before and after storage) is A1 formula with polyvinyl pirolidon 2 %, A2formula with polyvinyl pirolidone 2,5 % and B1 formula with CMC 2,0 %. Generally the result shows that the local binding agents give a bit lower performance as adjuvant compared with the existing water dispersible granule formulations.